2021
DOI: 10.1007/s13203-021-00282-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hybrid solvents featuring choline chloride-based deep eutectic solvents and ethanol as extractants for the liquid–liquid extraction of benzene from n-hexane: towards a green and sustainable paradigm

Abstract: Deep eutectic solvents (DESs) have high viscosities, but known to be mitigated by addition of suitable co-solvent. The effect of such co-solvent on the extraction efficiency of the hybrid solvent is hardly known. This study examined the effect of ethanol on three choline chloride-based DESs (glyceline, reline, and ethaline) by mixing each in turn with ethanol in various volume proportions. The hybrid solvents were evaluated for the extraction of benzene from n-hexane. Pseudo-ternary liquid–liquid equilibrium d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The addition of the co‐solvent with a certain range of molar ratios between the co‐solvent and IL decreased the fraction of free ions in the system rather than promoting the dissociation of the IL. In another previous study, ethanol‐incorporated ChCl‐polyol DES systems showed higher solubility of aromatics compared with the binary DES 37 . Since ethylene glycol leads to higher lignin solubility than water, higher delignification with ChCl‐DHBA‐EG was expected.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…The addition of the co‐solvent with a certain range of molar ratios between the co‐solvent and IL decreased the fraction of free ions in the system rather than promoting the dissociation of the IL. In another previous study, ethanol‐incorporated ChCl‐polyol DES systems showed higher solubility of aromatics compared with the binary DES 37 . Since ethylene glycol leads to higher lignin solubility than water, higher delignification with ChCl‐DHBA‐EG was expected.…”
Section: Resultsmentioning
confidence: 79%
“…In another previous study, ethanol-incorporated ChCl-polyol DES systems showed higher solubility of aromatics compared with the binary DES. 37 Since ethylene glycol leads to higher lignin solubility than water, higher delignification with ChCl-DHBA-EG was expected.…”
Section: Impact Of the Third Constituent Inmentioning
confidence: 99%
“…In the previous study, ethanol-incorporated ChCl-polyol DES systems showed higher solubility of aromatics compared to the binary DES. 37 Since ethylene glycol leads to higher lignin solubility than water, higher delignification with ChCl-DHBA-EG was expected. Interestingly, delignification yields of WT and TG sorghum stover by ethylene glycol-incorporated ternary DES (ChCl-DHBA-EG) were 38% and 34%, respectively, which were higher than binary DES.…”
Section: Determination Of the Molar Ratio Between Chcl And Dhbamentioning
confidence: 99%